Temperature effect on the interaction of polyethylene glycol with membranes and orientation order of cytoskeleton proteins in human erythrocytes - Zemlianskykh, Nina; Babijchuk, Lyubov (Problems of Cryobiology and Cryomedicine, 2026)
The study identified discrepancies in the modification of erythrocyte membrane upon exposure to polyethylene glycol with a molecular weight of 1500 (PEG) at various temperatures (4 and 37 °C) using the fluorescent probe 4-(n-dimethylaminostyryl)-1-methylpyridinium-n-toluenesulfonate (DSM), as well as alterations in the orientation order of proteins in the membrane-cytoskeleton complex using polarization microscopy. Exposure of erythrocytes to PEG at 37 °C caused complete disappearance of the hydrophobic component from the DSM fluorescent spectrum due to competition between PEG and DSM molecules for binding sites. Lowering the exposure temperature of cells to a cryoprotective agent (CPA) to 4 °C reduced the possibility of its hydrophobic contacts with cell membranes attested by the presence of the hydrophobic component in the DSM spectrum, although at a lower level than in the control. The decrease in hydrophobic contacts of PEG to membranes upon a lowering temperature at the stage of erythrocyte exposure to CPA provided retaining to a large extent the orientation order of the membrane cytoskeleton molecules both under the incubation process with CPA and after freeze–thawing of cells. Probl Cryobiol Cryomed. 2026; 36(1): 16—26.